Investigating the Effect of Parenting Type on Self-esteem and Perfectionism with the Mediating Role of Character Strengths on Adolescents with Anxiety Disorders - Khodadadi, Elahe; Zarshenas, Helia; Ahmadi, Saghar; Aghchi, Arash; Keneshloo, Roya (Shahroud Journal of Medical Sciences, 2024)
Background: Anxiety disorders are prevalent mental disorders that typically emerge during the early stages of one's life, with over 50% of occurrences happening before the age of 18. This study aimed to examine how different parenting styles impact the self-esteem and perfectionistic tendencies of adolescents dealing with anxiety disorders, while also considering the mediating influence of character strengths. Methods: This study is a combination of descriptive-correlational research and cross-sectional research methods, with the utilization of structural equation modeling (SEM). The statistical population for this study consisted of all teenagers (both boys and girls) in Tehran who were diagnosed with anxiety disorders during the period from July to October 2023. The statistical sample for this study consisted of 122 teenagers with anxiety disorders who were chosen through purposive sampling. The research instruments utilized were the Coopersmith Self-esteem Inventory (SEI), the Positive and Negative Perfectionism scale (PANPS), Baumrind's Parenting Styles Questionnaire (PSQ), and the Values In Action Inventory of Strengths (VIA-IS). The research data was analyzed using SPSS version 27 software, while the path between variables was analyzed using SmartPLS version 4 software. The significant level was set at 0.05. Results: Findings indicate that there was no significant relationship between authoritarian parenting and negative perfectionism, positive perfectionism, and self-esteem when considering the mediating role of character strengths (P-value>0.05). On the other hand, there was a positive and significant relationship between authoritative parenting and positive perfectionism, as well as self-esteem, when considering the mediating role of character strengths (P-value<0.001). Conclusions: The findings of the current investigation indicate that each of the three parenting styles contributes to the development of negative perfectionism. Additionally, the factor of personality strengths promotes self-confidence and positive perfectionism, while reducing negative perfectionism in teenagers. The outcomes of this study also emphasize the significant role of character strength as a mediating variable.